Orthodontic Treatment of Binder Syndrome: A Case Report with 5 Years of Follow-up. (July 2015) - Cossellu, Gianguido; Biagi, Roberto; Faggioni, Giulia; Farronato, Giampietro
We report here the case of orthodontic nonsurgical treatment in a patient with Binder syndrome. This rare syndrome (<1/10, 000) is a deforming alteration of the middle third of the face, also known as maxillonasal dysplasia/dysostosis. The therapeutic approach often undertaken is an orthodontic-surgical protocol, which includes several invasive interventions such as LeFort I or II. In this patient and early diagnosis made it possible to intervene on an orthodontic level only, thus avoiding highly invasive surgical procedures (as of a 5-year follow-up).